Concurrent vs. sequential chemoradiotherapy: a survival boost for lung cancer patients - Jinbiao Xu; Qiao Ji; Jianxiong Deng; Feng Yu (BioMedical Engineering OnLine)
Abstract Objective To investigate the clinical efficacy, incidence of radiation pneumonitis, and impact on lung function of sequential chemoradiotherapy (SCRT) and concurrent chemoradiotherapy (CCRT) in the treatment of lung cancer. Method From January 2020 to December 2022, 158 patients with non-small cell lung cancer (NSCLC) were admitted to our hospital and chosen as the study subjects. Their clinical data were analyzed retrospectively and organized into a control group (n = 78, received SCRT) and an observation group (n = 80, received CCRT). Lesion sizes measured through CT scans were used to compare the clinical efficacy between the two groups. The study also compared the rates of adverse reactions, radiation pneumonitis, and lung function pre- and post-treatment, including forced expiratory volume in one second (FEV1), forced vital capacity (FVC), and FEV1/FVC ratio. The comparison of serum tumor marker levels was conducted between two groups, with patients being observed over a 36-month period. Kaplan–Meier survival curves were used to analyze the changes in overall survival rate (OSR), progression-free survival (PFS), and overall survival (OS) between two groups of patients. Results For the observation group, the remission rate was 90.00%, and for the control group, it was 74.36%. The control rates were 96.25% for the observation group and 89.74% for the control group. Significantly higher remission and control rates were observed in the observation group than in the control group (P < 0.05). The hemoglobin reduction grade 0 was 81.2% in the observation group, compared to 58.9% in the control group. In terms of leukopenia reduction (grades 0–III) and hemoglobin reduction (grades 0–II), the observation group outperformed the control group (P < 0.05). In the observation group, 25.00% of patients experienced radiation pneumonitis, a higher rate compared to the 8.97% in the control group (P < 0.05). Overall, the control group experienced more severe radiation-induced lung injury compared to the observation group, with 6.41% of cases reaching grade IV, unlike the 0.00% in the observation group. Grade II accounted for 1.28% in the control group, a figure significantly lower than the 21.25% in the observation group (P < 0.05). Post-treatment, the FEV1, FVC, and FEV1/FVC values rose in both groups, with the observation group displaying significantly greater increases than the control group (P < 0.05). Also, after treatment, there was a decrease in CA125, SCC Ag, and CYFRA21-1 levels in both groups, with the observation group having significantly lower levels than the control group (P < 0.05). According to the Kaplan–Meier survival curve analysis, the observation group achieved an OSR of 90.00%, which exceeded the 83.33% of the control group (P > 0.05). Furthermore, PFS and OS levels were elevated in the observation group relative to the control group (P < 0.05). Conclusion CCRT could optimize the treatment effect for NSCLC patients by improving lung function, reducing serum tumor marker levels, and prolonging survival without increasing toxicity. Nonetheless, the occurrence of radiation pneumonitis was somewhat above expectations, and the treatment plan should be tailored to the patient's specific circumstances in clinical practice.